Aplikasi Pupuk Organik Cair Daun Ketapang dan Penambahan Kapur Dolomit pada Media Tercekam Garam untuk Pertumbuhan dan Hasil Panen Kentang Hitam (Plectranthus rotundifolius) - Fatmawati, Mitha Amanda; Andriani, Vivin; Ajiningrum, Purity Sabila (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Black potato production in Indonesia is limited, due to suboptimal cultivation techniques for black potato tubers. Potatoes are generally planted at an altitude above 1000 meters above sea level, because they require low temperatures during the planting process. The aim of this research is to determine the effect of applying liquid organic fertilizer (POC) from ketapang leaves and dolomite lime (CaMgCO3)2 with salt stress media on the growth and yield of black potato plants (Plectranthus rotundifolius). The type of experiment in this research was experimental research using a Randomized Group Design (RAK) which was carried out with 16 treatments, and was repeated 3 times. POC treatment of Ketapang leaves (K) with each concentration, namely K0 (0%), K1 (40%), K2 (60%), K3 (80%), and dolomite lime treatment (C) with each concentration , namely C0 (0g), C1 (20g), C2 (40g), and C3 (80g). Observation variables include plant growth parameters (plant height, number of leaves, stem diameter, and number of branches) and harvest yield parameters (number of tubers and tuber weight). Data analysis used the ANOVA test with a significance level of 0.05. The results of the research showed that giving POC ketapang leaves and dolomite lime had a significant effect on the growth and yield of black potatoes. At plant height, the yield was 24.00 cm, the number of leaves was 25, the number of branches was 5, the stem diameter was 0.90 mm, the number of tubers was 26, and the weight of the tubers was 232 grams.